2015
DOI: 10.1002/ajh.24195
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding spectrum in children with moderate or severe von Willebrand disease: Relevance of pediatric‐specific bleeding

Abstract: The bleeding phenotype of children with von Willebrand disease (VWD) needs to be characterized in detail to facilitate diagnosis during childhood and aid in the planning and assessment of treatment strategies. The objective was to evaluate the occurrence, type, and severity of bleeding in a large cohort of children with moderate and severe VWD. We included 113 children (aged 0-16 years) with Type 1 (n 5 60), 2 (n 5 44), and 3 (n 5 9) VWD with von Willebrand factor (VWF) antigen and/or VWF ristocetin cofactor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 34 publications
(47 reference statements)
2
63
0
1
Order By: Relevance
“…It develops by a variety of mechanisms in such acquired disorders but typically resolves with the treatment of the underlying disease or cause. 63 Several factors influence the symptoms of Von Willebrand disease: Plasma level of residual Von Willebrand factor activity, disease type and subtype and also age and sex of the patient. Bruising and epistaxis are the prominent symptoms in children with Von Willebrand disease.…”
Section: Discussionmentioning
confidence: 99%
“…It develops by a variety of mechanisms in such acquired disorders but typically resolves with the treatment of the underlying disease or cause. 63 Several factors influence the symptoms of Von Willebrand disease: Plasma level of residual Von Willebrand factor activity, disease type and subtype and also age and sex of the patient. Bruising and epistaxis are the prominent symptoms in children with Von Willebrand disease.…”
Section: Discussionmentioning
confidence: 99%
“…Type 3 patients have the highest bleeding scores, type 2 patients are intermediate, and type 1 patients have the lowest bleeding scores. 9 In addition, lower VWF:Ag and FVIII have been associated with increased bleeding scores. 10 However, obtaining a bleeding score on a patient who has previously been diagnosed and received treatment may be difficult, as treatment in and of itself will raise the bleeding score.…”
Section: Bleeding Assessment Toolsmentioning
confidence: 99%
“…Inclusion of pediatric-specific questions may be helpful but does not always provide complete reassurance that a given patient will not develop bleeding in the future. 9 In addition, some studies are complicated by the fact that bleeding scores rely on the worst historical episode to generate points; a patient who receives a diagnosis of VWD and is subsequently treated for surgery can generate an increased bleeding score independent of their recent symptoms because of that treatment. Because VWF levels increase with age, 12 it is possible that a patient might "outgrow" their diagnosis.…”
Section: Bleeding Assessment Toolsmentioning
confidence: 99%
“…VWD is caused by reduced von Willebrand factor (VWF) levels (type 1), an abnormal function of VWF (type 2) or a complete absence of VWF (type 3) . Although VWD is clinically mainly characterized by mucocutaneous bleeding, all types of bleeding can occur . We previously found that adults and children with VWD have a lower health‐related quality of life (HRQoL) compared to the general population .…”
Section: Introductionmentioning
confidence: 99%